Introductory Computer Forensics - Lin, Xiaodong (Springer, 2018)
Internet technology is advancing at a speed beyond comprehension. With everadvancing Internet technology, we truly are living in a digital age. It will certainly improve our quality of life, as it can offer the speed, the capabilities, to handle endless different types of transactions at relatively low cost. Things we take for granted in our daily activities are an excellent example: transferring money, surfing, emailing, sharing information, etc. On the other hand, we will become handicap in our daily life if without Internet. Simply put it, we all depend on the capabilities of Internet technology to run our daily errands more efficiently, even when we do not directly notice it. Unfortunately, one of Murphy’s more applicable axioms becomes apparent with this technology: “with every solution comes a new set of problems.” This marvelous new technology will also provide golden opportunities for organized crime groups, as well as other individuals who want to abuse the technology and maximize their profit illegally. Activities like denial of service attacks, website vandalism, online fraud, money laundering, and more have surfaced. We have all read headlines from around the world about companies being hacked and losing personal information; cybercrimes have become a rampant reality that we must all face, and according to the forecast, the cybercrime trends will worsen globally, and billions of dollars will be lost every year in the global conflict against it. In order to fight against cybercrime effectively, public prosecutors need to be able to do more than simply match a crime to a suspect; they must be able to produce convincing digital evidence in a court of law, before a judge who may not even know what a USB drive is, in order to put the criminals behind bars. This evidence may include all computer log files, corresponding emails, accounting information, spreadsheets, and other related records, regardless of whether or not these files were deleted or not. According to the study, the majority of digital evidence presented in court is obtainable from all sorts of the daily used electronic devices such as computer, digital camera, BlackBerry, and 3G cell phones.
A Hands-on Practical Approach
Keywords: Digital forensic science